Pelatihan Kewirausahaan Hijau: Pembuatan Lilin Aromaterapi dari Minyak Jelantah bagi Murid Panti Asuhan Putri Aisyiyah Malang - Adriana Sari, Padma; Sumiadji, Sumiadji; Fitriana, Annisa; Amalia, Riezky; Isrowiyah, Anna; Arisudhana, Aditya (J-Dinamika : Jurnal Pengabdian Masyarakat, 2026)
Used cooking oil is a household and culinary industry waste that has the potential to pollute the environment if not properly processed. The Aisyiyah Girls’ Orphanage in Malang, which operates a catering business, produces approximately 30 liters of used cooking oil per month. This community service activity aims to provide education on processing used cooking oil into marketable products in the form of aromatherapy candles, as well as to foster an entrepreneurial mindset among the orphanage children. The implementation methods include raising awareness about the dangers of used cooking oil and conducting hands-on training in making aromatherapy candles using additional materials such as paraffin, coloring agents, and essential oils. The results of the activity showed an increase in participants’ knowledge of waste management and their skills in producing aromatherapy candles. Participants also showed interest in continuing production independently. This program provides dual benefits in terms of waste reduction and economic empowerment.